2006
DOI: 10.2217/14622416.7.7.987
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the ABCB1 Gene are Associated with the Therapeutic Response to Risperidone in Chinese Schizophrenia Patients

Abstract: P-glycoprotein, a product of the ATP-binding cassette B1 (ABCB1) gene, plays an important role in absorption and distribution of drugs. The brain entry of risperidone and 9-OH-risperidone is greatly limited by P-glycoprotein, which implies that the functional polymorphisms of ABCB1 in humans may be a factor contributing to the variability in response to risperidone. The present study was therefore designed to examine whether polymorphisms of the ABCB1 gene are related to therapeutic response. For this purpose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 33 publications
1
40
2
3
Order By: Relevance
“…40 Our results show that the ABCB1 c.1236C4T polymorphism influences risperidone clinical improvement, with patients carrying the T allele showing better improvement, in agreement with an earlier study. 41 The 1236T allele, which has been associated with lower expression and function of P-glycoprotein in the blood-brain barrier and in the small intestine, [42][43][44] would lead to a lower efflux of risperidone and hence higher drug concentration in the brain, therefore explaining the better outcome of the patients carrying this allele. The silent Abbreviations: EM, extensive metabolizers; PM, poor metabolizers, UM, ultra-rapid metabolizers.…”
Section: Pharmacogenetics Of Risperidone In Autismmentioning
confidence: 99%
“…40 Our results show that the ABCB1 c.1236C4T polymorphism influences risperidone clinical improvement, with patients carrying the T allele showing better improvement, in agreement with an earlier study. 41 The 1236T allele, which has been associated with lower expression and function of P-glycoprotein in the blood-brain barrier and in the small intestine, [42][43][44] would lead to a lower efflux of risperidone and hence higher drug concentration in the brain, therefore explaining the better outcome of the patients carrying this allele. The silent Abbreviations: EM, extensive metabolizers; PM, poor metabolizers, UM, ultra-rapid metabolizers.…”
Section: Pharmacogenetics Of Risperidone In Autismmentioning
confidence: 99%
“…A naturalistic study by Vijayan et al found that individuals with 3435CC (rs1045642) and 1236CC (rs1128503) genotypes responded better to a variety of APs, using the BPRS scale (93). Notably, earlier monotherapy studies in other populations found that individuals with the 3435TT genotype showed better response to olanzapine (94), and those with the 1236TT polymorphism showed better response to risperidone (95). On the contrary, Crisafulli et al did not observe an association between ABCB1 and response in a Korean population treated with a variety of APs using the PANSS scale (96).…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…[5][6][7][8][9][10] A total of 127 unrelated schizophrenia patients (45 males and 84 females; mean±SD age: 36.1±11.1 years) were recruited from the Shanghai Mental Health Center on the basis of the following inclusion criteria: (1) had no physical complications or other psychiatric disorders; (2) had no history suggesting that antipsychotic treatment would be ineffective; (3) satisfied the DSM-IV criteria for schizophrenia; and (4) had not received any medication for 4-6 weeks before this study. All subjects gave signed, written informed consent through their responsible relatives before the study.…”
Section: Clinical Samplementioning
confidence: 99%
“…3,4 Genetic factors are commonly considered to be the main cause of these interindividual differences. [5][6][7][8][9][10] Previous studies have demonstrated that the expression levels of the human brain-derived neurotrophic factor (BDNF) gene in the prefrontal cortex, hippocampus are decreased in schizophrenic patients. 11 Clinical psychopharmacological and animal model-based experiments have also shown that antipsychotics can regulate the expression of BDNF.…”
Section: Introductionmentioning
confidence: 99%